Rare bird documentation form for Greater Scaup at Lock and Dam 9, 1983 - Myers, Robert K.et al (1983)
Rare bird documentation form for four Greater Scaups at Lock and Dam 9 in Allamakee County, IA on November 21, 1983. Epson - sheet feed